Ilmiy tadqiqotchilik faoliyatini amalga oshirish mexanizmi - Otayeva, S.S (SCIENCE and SOCIETY, 2023)
The article analyzes the content of scientific research activity and modern requirements for its compo- nent, as well as ways to achieve their effectiveness in the process of scientific activity.
Keywords: scientific research; science; reflex; reaction; hypothesis; competence approach; experience; pedagogical ability; creative ability